2017
DOI: 10.1155/2017/4969076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Chestnut or Quebracho Tannin Supplementation on Microbial Community and Fatty Acid Profile in the Rumen of Dairy Ewes

Abstract: Ruminants derived products have a prominent role in diets and economy worldwide; therefore, the capability to control the rumen microbial ecosystem, for ameliorating their quality, is of fundamental importance in the livestock sector. The aim of this study was to evaluate the effect of dietary supplementation with chestnut and quebracho tannins on microbial community and fatty acid profile, in the rumen fluid of dairy ewes. Multivariate analysis of PCR-DGGE profiles of rumen microbial communities showed a corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…The increased relative abundance of these and other genera such as Parabacteroides in the mucin (succinate producer) may confirm the indirect positive reinforcement of the PPC on the overall community (Supplementary Table 5C). Moreover, Hungatella has been reported to thrive on medium used to produce probiotic bacteria (Kaur et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The increased relative abundance of these and other genera such as Parabacteroides in the mucin (succinate producer) may confirm the indirect positive reinforcement of the PPC on the overall community (Supplementary Table 5C). Moreover, Hungatella has been reported to thrive on medium used to produce probiotic bacteria (Kaur et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Commonly, condensed tannins decrease the rumen degradation of fibre because they induce important changes in the microbial community, while the effect of hydrolysable tannins is usually milder [40]. Chestnut tannin extract has been reported to be less effective on the growth of cellulolytic bacteria than condensed tannins, such as quebracho or mimosa [11,12,40,41]. A plausible explanation for this behaviour could be related to the higher grade of depolymerization of hydrolysable tannins in rumen compared to condensed tannins [42].…”
Section: Discussionmentioning
confidence: 99%
“…Data reported in literature showed that the use of CHT in ruminant feeding might result in changes in the profile of rumen microbial community [9,11,12]. Vescalagin is the main active component present in CHT [13], while GAL is quickly released in rumen liquor (RL) by hydrolysis of CHT [14].…”
Section: Introductionmentioning
confidence: 99%
“…In tropical plants, phenolic components have a more massive concentration than plants in temperate climates.This is caused by exposure to ultraviolet rays in high intensity (Berli et al 2011). In vitro studies have shown convincing results that the phenolic component can reduce C18: 0 accumulation in rumen fluid and increase conjugated linoleic acid (CLA) isomers (Vasta et al 2009;Ishlak et al 2015;Buccioni et al 2017). The same results were shown in an in vivo study where polyphenol supplementation affected the biohydrogenation of PUFA and the composition of the rumen microbiota by increasing intermediate fatty acids such as cis-9, trans-11 C18: 2 (Vasta et al 2010;Andres et al 2016;Yusuf et al 2017).…”
Section: Biohydrogenation Reduction Agentsmentioning
confidence: 99%